Analysis of Different Flow Regime on Spillway Stepped Chute - Zahari N.M.; Hizami A.; Zawawi M.H.; Abas A.; Rashid M.M.R.; Azman A. (Springer, 2023)
Roller Compacted Concrete (RCC) is becoming an increasingly popular method of building and protecting dam embankments. Numerous RCC spillways have been built worldwide and Murum Dam is one of the RCC spillways that have been built in Sarawak, Malaysia. This paper will discuss on analysis of different flow regime that occur at stepped spillways in Murum Dam using numerical simulation. This study consists of creating the three-dimensional model of the spillway and run a simulation by inserting different velocity for different type of flow. Flow regime in stepped are divided into three type which is nappe, transitional and skimming flow. The simulation shows that nappe, transitional and skimming flow occur in both laminar and turbulent flow even different input in velocity. The results show turbulence model have the highest velocity of 361.38m/s and highest pressure 6.5 107 Pa. 2020, Springer Nature Singapore Pte Ltd.